MITOS DALAM KAMPANYE POLITIK : Analisis Semiotika Roland Barthes Pada Film Our Brand is Crisis - Afnira, Ella (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2023)
One form of audio-visual mass media that is capable of conveying information effectively is a film, both in the form of fiction and documentary. Mass art, especially film, can bring a picture of the contemporary world to the public at large, increase political awareness, encourage world surveillance, and bring social critical images. Through film, directors can convey messages and raise a phenomenon that occurs in society. Roland Barthes's semiotic analysis is very relevant to use in studying a film because a film consists of various interrelated signs. The signs include various sign systems that work together to achieve the desired effect. In Roland Barthes' semiotic analysis, the film has a meaning consisting of a signifier and a signified. The research method used is qualitative with primary data sources from the film Our Brand Is Crisis. Researchers used data collection techniques through observation and documentation. Roland Barthes' Semiotic Analysis in this study is used to interpret the meaning of the signs in the film, which consists of five stages: identifying signs, analyzing denotative and connotative meanings, determining social, cultural, and historical contexts, and analyzing the myths contained in signs. the. The goal is to understand and express meaning in film and how the social and cultural context shapes it.